The Potential Role of The Nuclear Factor Erythroid 2–Related Factor 2 Depletion on Gonadotropin-Releasing Hormone Imbalance in Polycystic Ovarian Syndrome Iraqi Patients - N. Hameed, Zaman; M. Rashied , Rashied; M. Kareem, Sawsan (Bogor Agricultural University, Indonesia, 2025)
The nuclear factor erythroid 2-related factor 2 (Nrf2) is a master regulator of most cytoprotective genes that respond to oxidative stresses. Thus, Nrf2 depletion is usually associated with excessive oxidative stress (OS). We sought to assess Nrf2 concentration as an indicator of elevated OS in women with PCOS. Likewise, study the effects associated with this depletion on the balance of gonadotropin-releasing hormone (GnRH). The case-control study comprised ninety women of reproductive age. Our results revealed that women with PCOS had significantly higher blood Nrf2 depletion compared with the non-PCOS group (P = 0.000). So, there was a significant increase in both Luteinizing hormone (LH) concentration and LHratio (P = 0.000 and P = 0.007, respectively. In the PCOS group, Nrf2 depletion was adversely correlated with elevated LH level (-0.551) at (P = 0.012), and elevated LHratio (-0.628) at (P = 0.003), infertility (-0.460) at (p = 0.041) and menstrual irregularity (-0.575) at (P = 0.008). Meantime, according to the odds ratio analysis, Nrf2 depletion had a high relative risk in the etiology of syndrome 0.967 (0.932–0.945) at (P = 0.048). In conclusion, Nrf2 depletion had a role in the GnRH imbalance in PCOS through several mechanisms. Thus, we can suggest that enhancing the Nrf2 pathway can be a possible therapeutic approach for PCOS treatment.